Paket Intervensi Stunting terhadap Keterampilan Kader Posyandu dalam Pencegahan Stunting pada Balita - Erna Julianti; Elni Elni (Jurnal Keperawatan Silampari, 2022)
posyandu cadres in preventing stunting in toddlers-Quantitative Research Methods with a quasi-experimental approach pre-test and post-test without control. The results showed that the average length or height measurement skills and breastfeeding technique skills performed by posyandu cadres in stunting prevention after receiving the stunting intervention package were 11.29 and 11.40 higher than before the stunting intervention package at 7.89. and 8.06. The analysis results showed a significant difference between the average skills of posyandu cadres in stunting prevention before and after being given the stunting intervention package with p values ​​of 0.001 and 0.001. In conclusion, there is a significant difference between the average skills of posyandu cadres in stunting prevention before and after being given the stunting intervention package. Keywords: Posyandu Cadre, Stunting Intervention Package (PIS), Stunting